2021
DOI: 10.1038/s41524-020-00474-5
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic mechanism of unusual lattice thermal transport in TlInTe2

Abstract: We investigate the microscopic mechanism of ultralow lattice thermal conductivity (κl) of TlInTe2 and its weak temperature dependence using a unified theory of lattice heat transport, that considers contributions arising from the particle-like propagation as well as wave-like tunneling of phonons. While we use the Peierls–Boltzmann transport equation (PBTE) to calculate the particle-like contributions (κl(PBTE)), we explicitly calculate the off-diagonal (OD) components of the heat-flux operator within a first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 70 publications
(121 reference statements)
2
25
0
Order By: Relevance
“…The calculated phonon dispersion (Figure a) at the optimized lattice constants exhibits a localized low-frequency optical phonon branch (∼30 cm –1 ) that primarily originates due to the vibrations of Ag and Se atoms (see phonon density of states in Figure b). The low-frequency localized phonon modes can effectively scatter the heat-carrying phonons, inducing a low κ lat in crystalline solids. , Interestingly, the low-energy branch exhibits phonons at very low frequency (∼4 cm –1 ) at S and Z points which are very sensitive to strain and hence effective in reducing κ lat of (SnSe) 0.5 (AgSbSe 2 ) 0.5 in a way similar to the overdamped phonons that induce ultralow κ lat in CsPbBr 3 . This 4 cm –1 mode predominantly involves vibration of the Se atom, which prompted us to off-center Se during X-PDF analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated phonon dispersion (Figure a) at the optimized lattice constants exhibits a localized low-frequency optical phonon branch (∼30 cm –1 ) that primarily originates due to the vibrations of Ag and Se atoms (see phonon density of states in Figure b). The low-frequency localized phonon modes can effectively scatter the heat-carrying phonons, inducing a low κ lat in crystalline solids. , Interestingly, the low-energy branch exhibits phonons at very low frequency (∼4 cm –1 ) at S and Z points which are very sensitive to strain and hence effective in reducing κ lat of (SnSe) 0.5 (AgSbSe 2 ) 0.5 in a way similar to the overdamped phonons that induce ultralow κ lat in CsPbBr 3 . This 4 cm –1 mode predominantly involves vibration of the Se atom, which prompted us to off-center Se during X-PDF analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we show the eigen displacement for (i) the damped phonon mode (4 cm –1 ) at the S point where only the Se atoms vibrate (Figure g) and (ii) localized phonon mode (12 cm –1 ) at the Γ point in Figure h, where the Ag atoms have the largest displacements. Such localized phonon modes are a strong source of phonon scattering processes in the material. , Hence the presence of such localized low frequency optical modes, high anharmonicity within the lattice, and local off-centering of the Se atom contributes heavily to scatter the heat carrying acoustic phonons, and as a result, low κ lat is observed for (SnSe) 0.5 (AgSbSe 2 ) 0.5 .…”
Section: Resultsmentioning
confidence: 99%
“…There are several mechanisms which alone or jointly can lead to glass-like thermal conductivities in crystalline materials: disorder, anharmonicity, and complex crystal structure. [37,40,41,42] Disordered crystals such as single crystal Zr 0.85 Y 0.15 O 1.925 have glass-like thermal conductivity even though its fluorite crystal structure is not particularly complex. [37] Recent theoretical studies have revealed that the combination of strong anharmonicity and unit cell complexity can lead to glass-like thermal conductivity without disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Soon after the discovery of non-trivial topological quantum states in chalcogen-based semiconductors with narrow band gaps and strong spin–orbit coupling (SOC), the two-dimensional (2D) layered semiconductors opened up a new avenue to scrutinize novel pressure-induced phenomena, such as quantum phase transitions, topological superconductors, charge density waves, structural phase transitions, Lifshitz transitions, and so forth. In contrast to layered 2D materials, one-dimensional (1D) chain materials from the TlSe family such as TlInTe 2 , TlInSe 2 , TlGaTe 2 , and so forth are relatively under-explored from the perspective of high pressure research, , although they exhibit astonishing properties at ambient pressure. For instance, TlInSe 2 exhibits exceptionally high thermoelectric properties, which is correlated to the formation of an incommensurate superlattice . TlInTe 2 exhibits a high figure of merit (1.78 for p-doped and 1.84 for n-doped at 300 K) with an intrinsic ultra-low lattice thermal conductivity (<0.5 W/mK in the temperature range 300–673 K) owing to the spatial fluctuation of the Tl 1+ cation inside the polyhedral framework of a sublattice formed by Tl 1+ and Te 2– ions. ,, …”
Section: Introductionmentioning
confidence: 99%